Misconception protist in high school biology textbooks - Defita Raharjo; Murni Ramli; Yudi Rinanto (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Protist one of the difficult subject to be understood by students because it is an abstract and the objects are microscopic. Textbook is used in the teaching learning process as a resource for students to understand the concepts. If there are any error information are written in the textbook,it may cause misconceptions for the student. The aims of this study are to identify the misconceptions in high school biology textbook and predict the impacts of misconceptions. This study is a document analysis, two textbooks were selected purposively among the textbooks used in the high schools in Klaten Regency, Indonesia. Analysis of misconceptions based on five categories according to Hershey, namely undergeneralization, obsolute concepts and terms, oversimplification, overgeneralizations and misidentifications. The result show that there was found one misconception category in the textbooks, namely undergeneralization 14,28% in book D and by 10,71% in book E. Undergeneralization will make the students only understand a part of concepts or problems in the material of protist